An open‐label, single‐arm, multicenter, phase II trial of bireociclib as monotherapy for heavily pretreated HR‐positive, HER2‐negative advanced breast cancer patients: BRIGHT‐1 trial - Jiayu Wang; Qingyuan Zhang; Tao Sun; Huiping Li; Ying Cheng; Zhongsheng Tong; Huihui Li; Wei Li; Jingfen Wang; Yuee Teng; Xinhong Wu; Jing Cheng; et al. (Cancer Communications)
Abstract Background Bireociclib (XZP‐3287) is a novel selective cyclin‐dependent kinase 4 and 6 (CDK4/6) inhibitor, with a favorable safety profile demonstrated in preclinical and phase I studies. BRIGHT‐1 aimed to further explore the efficacy and safety of bireociclib monotherapy in patients with locally advanced, recurrent or metastatic, hormone receptor‐positive and human epidermal growth factor receptor 2‐negative (HR+/HER2−) breast cancer who had progressed on or after prior chemotherapy and endocrine therapy in advanced settings, without previous exposure to CDK4/6 inhibitors. Methods In this open‐label phase II trial, eligible patients received bireociclib 480 mg twice daily (BID) until disease progression or intolerable toxicities. The primary endpoint was the confirmed objective response rate (ORR) assessed by an independent review committee (IRC). The secondary endpoints included progression‐free survival (PFS), investigator‐assessed ORR, disease control rate (DCR), clinical benefit rate (CBR), duration of response (DoR), overall survival (OS), safety and the pharmacokinetic properties of bireociclib. Results A total of 131 patients were enrolled. At data cutoff (July 31, 2023), the IRC‐assessed ORR was 29.8% (95% confidence interval [CI], 22.1% to 38.4%), with a DCR of 73.3% (95% CI, 64.8% to 80.6%), CBR of 42.0% (95% CI, 33.4% to 50.9%) and a median DoR of 15.2 months (95% CI, 9.5 months to not reached). The median PFS was 11.0 months (95% CI, 7.3 months to 12.9 months) assessed by the IRC, and the median OS was 29.0 months (95% CI, 24.9 months to not reached). The most frequently reported treatment‐emergent adverse events (TEAEs) of any grade were diarrhea (93.1%), neutrophil count decreased (87.0%), white blood cell decreased (86.3%), vomiting (78.6%), anemia (72.5%), and platelet count decreased (72.5%). The grade ≥3 TEAEs occurred in 109 (83.2%) patients. The most common grade ≥3 TEAEs were neutrophil count decreased (43.5%), white blood cell decreased (32.8%), hypokalemia (20.6%), and diarrhea (19.1%). Conclusions Bireociclib monotherapy at 480 mg BID exhibited promising and sustained clinical activity, with no unexpected and acceptable toxicity in patients with recurrent or metastatic HR+/HER2− breast cancer who had progressed on or after previous therapy. Trial registration Clinicaltrials.gov ID, NCT04539496.